Nano-material-containing bridging agent for coating and preparation method thereof
By combining composite nanomaterials with polyisocyanate base materials, the bridge mount agent for coatings prepared solves the problem of limited performance improvement effect of bridge mount agents in the prior art, and a significant improvement in the high adhesion, hardness, wear resistance and corrosion resistance of the coating are achieved.
Patent Information
- Application Number
- CN202411921536.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The bridge studs prepared by the prior art have limited effects in improving the performance of the coating, limiting their application in some special fields.
Combining composite nanomaterials with polyisocyanate base materials is used to prepare a bridge-building agent containing nanomaterials for coatings. The composite nanomaterial is prepared by heat treatment, grinding and uniform dispersion, and the mass fraction of the nanomaterial is 7-8 wt%.
A stable three-dimensional mesh structure is formed through cross-linking reaction, which significantly improves the adhesion, hardness, wear resistance and corrosion resistance of the coating, extends the service life of the coating, and improves the water resistance of the coating.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a bridging agent containing nano materials for coatings and a preparation method thereof. Background Art
[0002] Paint, traditionally known as paint in China, is a viscous liquid coated on the surface of an object to be protected or decorated, and can form a continuous film that is firmly attached to the object. It is usually mainly resin, oil or emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water.
[0003] Paint bridging agent plays an extremely important role in the paint system. Adding an appropriate amount of bridging agent can improve the paint's leveling, drying speed and other construction properties, making the paint easier to operate during construction and obtaining a flatter and smoother coating surface.
[0004] However, the bridging agent prepared by the prior art has limited effect on improving the performance of coatings, which restricts its application in some special fields.
[0005] Based on this, we proposed a bridging agent containing nanomaterials for coatings, hoping to solve the shortcomings of the existing technology. Summary of the invention
[0006] 1. Technical problems solved
[0007] In view of the deficiencies in the prior art, the present invention provides a bridging agent containing nanomaterials for coatings and a preparation method thereof.
[0008] (II) Technical solution
[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: A bridging agent containing nano materials for coatings, which is made by mixing composite nano materials and base materials; Among them, the mass fraction of the composite nanomaterial is 7-8wt%, and the rest is the base material; The base material is: polyisocyanate.
[0010] As a further technical solution: the preparation method of the composite nanomaterial is: First, melamine is placed in a crucible, and then placed in a furnace for heating and heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; Grinding the preliminary material for 2-3 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture was evenly dispersed in a sulfuric acid solution, the temperature was adjusted to 60°C, and the mixture was stirred for 4 hours. Then, the mixture was filtered and centrifuged alternately in water and anhydrous ethanol, respectively, for 5 minutes in water and 10 minutes in anhydrous ethanol. Finally, the mixture was vacuum dried to obtain a composite nanomaterial.
[0011] As a further technical solution: the heat treatment temperature is 580-600°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
[0012] As a further technical solution: the mixing mass ratio of the abrasive, carbon nanotubes and nano-silicon dioxide is 3-5; 10:2.
[0013] As a further technical solution: the mixing ratio of the mixed material and the sulfuric acid solution is -0-15g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0014] As a further technical solution: the rotation speed of the alternating centrifugal treatment is 8000r / min.
[0015] As a further technical solution: the vacuum drying temperature is 60°C and the time is 10 minutes.
[0016] As a further technical solution: the polyisocyanate is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1-2:1.
[0017] A method for preparing a bridging agent containing nano materials for coatings comprises the following steps: adding composite nano materials and base materials into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes to obtain the bridging agent.
[0018] (III) Beneficial effects Compared with the prior art, the present invention provides a bridging agent containing nanomaterials for coatings, which has the following beneficial effects: After the bridging agent prepared by the present invention is added to the coating, it can undergo a cross-linking reaction with the resin component in the coating, thereby being able to form a more stable three-dimensional network structure, making the bonding force between the coating formed by the coating and the substrate stronger, greatly improving the adhesion of the coating, and making the coating less likely to fall off.
[0019] Through the cross-linking reaction between the bridging agent and the resin component in the coating, the molecular structure of the coating can be made tighter. Combined with the effect of the composite nanomaterial, the hardness and wear resistance of the coating can be further improved, enabling it to better resist external friction and scratches.
[0020] Through the introduction of bridging agents, the three-dimensional network structure formed can effectively block the invasion of external corrosive chemical components, so that the formed coating has better acid resistance, alkali resistance, solvent resistance and other corrosion resistance, greatly improving the service life of the coating.
[0021] The introduction of the bridging agent prepared by the present invention can also reduce the porosity of the coating, thereby reducing the penetration of water, thereby improving the water resistance of the coating, and can effectively prevent the problems of bubbling and shedding of the coating caused by water penetration. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0023] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 7wt% and the rest is the base material; The base material is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1:1.
[0024] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heating and heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 580°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
[0025] Grinding the preliminary material for 2 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered and centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 3:10:2.
[0026] The mixing ratio of the mixture and sulfuric acid solution is 10g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0027] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0028] The vacuum drying temperature was 60°C and the time was 10 min. Example 2
[0029] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 7.2wt%, and the rest is the base material; The base material is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1.2:1.
[0030] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 585°C, the heating temperature is 5°C / mi, and the slow cooling rate is 3°C / min.
[0031] Grinding the preliminary material for 2.5 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered and centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 3.5;10:2.
[0032] The mixing ratio of the mixture and sulfuric acid solution is 12g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0033] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0034] The vacuum drying temperature was 60°C and the time was 10 min. Example 3
[0035] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 7.5wt%, and the rest is the base material; The base material is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1.5:1.
[0036] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heating and heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 590°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
[0037] Grinding the preliminary material for 2 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered and centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 4;10:2.
[0038] The mixing ratio of the mixed material and sulfuric acid solution is 13g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0039] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0040] The vacuum drying temperature was 60°C and the time was 10 min. Example 4
[0041] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 7-8wt%, and the rest is the base material; The base material is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1.8:1.
[0042] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 590°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
[0043] Grinding the preliminary material for 3 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered and centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 4.5;10:2.
[0044] The mixing ratio of the mixture and sulfuric acid solution is 15g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0045] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0046] The vacuum drying temperature was 60°C and the time was 10 min. Example 5
[0047] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 7.8wt%, and the rest is the base material; The base material is: polyisocyanate; the polyisocyanate is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1.6:1.
[0048] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 595°C, the heating temperature is 5°C / mi, and the slow cooling rate is 3°C / min.
[0049] Grinding the preliminary material for 2 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered and centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 4.5;10:2.
[0050] The mixing ratio of the mixed material and sulfuric acid solution is 14g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0051] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0052] The vacuum drying temperature was 60°C and the time was 10 min. Example 6
[0053] A method for preparing a bridging agent containing nano materials for coatings, comprising adding a composite nano material and a base material into a mixer in proportion, stirring and mixing at a speed of 500 r / min for 30 minutes, wherein the composite nano material has a mass fraction of 8wt% and the rest is the base material; The base material is: polyisocyanate; the polyisocyanate is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 2:1.
[0054] The preparation method of composite nanomaterials is as follows: First, melamine is placed in a crucible and then placed in a melting furnace for heating and heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; the heat treatment temperature is 600°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
[0055] Grinding the preliminary material for 3 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture is evenly dispersed in a sulfuric acid solution, the temperature is adjusted to 60°C, and the mixture is stirred for 4 hours. Then, the mixture is filtered, and then centrifuged alternately in water and anhydrous ethanol, wherein the mixture is centrifuged in water for 5 minutes and in anhydrous ethanol for 10 minutes. Finally, the mixture is vacuum dried to obtain a composite nanomaterial; the mixing mass ratio of the abrasive, carbon nanotubes, and nano-silicon dioxide is 5;10:2.
[0056] The mixing ratio of the mixture and sulfuric acid solution is 15g:200mL; The mass fraction of sulfuric acid solution is 40%.
[0057] The rotation speed of the alternating centrifugal treatment is 8000r / min.
[0058] The vacuum drying temperature was 60°C and the time was 10 min.
[0059] The following is a comparative example: Comparative Example 1: On the basis of Example 1, no composite nanomaterial is added, and the rest of the technical solutions are consistent with the technical solutions of Example 1.
[0060] Comparative Example 2: On the basis of Example 1, the composite nano material is replaced by only an equal amount of nano-silicon dioxide, and the rest of the technical solutions are consistent with those of Example 1.
[0061] Comparative Example 3: On the basis of Example 1, the composite nanomaterial is only replaced by an equal amount of carbon nanotubes, and the rest of the technical solutions are consistent with those of Example 1.
[0062] test: By weight, 80 parts of water-based acrylic resin and 10 parts of silicone defoamer were mixed to obtain a test coating; The test coating, the embodiment and the comparative example bridging agent were mixed in a mass ratio of 10:1, uniformly coated on a glass plate, and cured at 60°C to form a film with a thickness of 0.2 mm. Each coating was tested separately; Pencil hardness test Conduct pencil hardness test on the coating according to the national standard "GB / T6739-1966 Coating pencil hardness determination method"; Table 1 Pencil hardness Example 1 3H Example 2 3H Example 3 3H Example 4 3H Example 5 3H Example 6 3H Comparative Example 1 1H Comparative Example 2 2H Comparative Example 3 2H It can be seen from Table 1 that the bridging agent prepared by the present invention can improve the surface hardness of the coating.
[0063] Test the water resistance of the coating according to GB / T1733-1993 method: Table 2 Water resistance (720h) Example 1 No bubbles, no shedding Example 2 No bubbles, no shedding Example 3 No bubbles, no shedding Example 4 No bubbles, no shedding Example 5 No bubbles, no shedding Example 6 No bubbles, no shedding Comparative Example 1 Blistering and shedding Comparative Example 2 No bubbles, no shedding Comparative Example 3 No bubbles, no shedding It can be seen from Table 2 that the water resistance of the coating can be improved after the bridging agent prepared by the present invention is introduced into the coating.
[0064] Flexibility test, measured in accordance with GB / T1731: Table 3 Flexibility mm Example 1 1.63 Example 2 1.58 Example 3 1.61 Example 4 1.65 Example 5 1.59 Example 6 1.57 Comparative Example 1 1.14 Comparative Example 2 1.49 Comparative Example 3 1.45 It can be seen from Table 3 that the bridging agent prepared by the present invention can improve the flexibility of the coating.
[0065] Impact strength is measured according to GB / T1732; Table 4 Impact strength / cm Example 1 55.2 Example 2 56.0 Example 3 53.8 Example 4 54.1 Example 5 55.4 Example 6 54.3 Comparative Example 1 32.7 Comparative Example 2 40.5 Comparative Example 3 42.9 It can be seen from Table 4 that the bridging agent prepared by the present invention can greatly improve the impact performance of the paint coating.
[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bridging agent containing nanomaterials for coatings, characterized in that: It is made of composite nanomaterials and base materials; Among them, the mass fraction of the composite nanomaterial is 7-8wt%, and the rest is the base material; The base material is: polyisocyanate.
2. The nanomaterial-containing bridging agent for coating according to claim 1, characterized in that: The composite nanomaterial preparation method is: First, melamine is placed in a crucible, and then placed in a furnace for heating and heat treatment. After the heat treatment is completed, it is slowly cooled to room temperature to obtain a preliminary material; Grinding the preliminary material for 2-3 hours to obtain a grind; The grinding speed is 550r / min; The grinding material, carbon nanotubes and nano-silicon dioxide are mixed together to obtain a mixed material; The obtained mixture was evenly dispersed in a sulfuric acid solution, the temperature was adjusted to 60°C, and the mixture was stirred for 4 hours. Then, the mixture was filtered and centrifuged alternately in water and anhydrous ethanol, respectively, for 5 minutes in water and 10 minutes in anhydrous ethanol. Finally, the mixture was vacuum dried to obtain a composite nanomaterial.
3. The nanomaterial-containing bridging agent for coating according to claim 2, characterized in that: The heat treatment temperature is 580-600°C, the heating temperature is 5°C / min, and the slow cooling rate is 3°C / min.
4. The nanomaterial-containing bridging agent for coating according to claim 2, characterized in that: The mixing mass ratio of the abrasive, carbon nanotubes and nano-silicon dioxide is 3-5; 10:
2.
5. The nanomaterial-containing bridging agent for coating according to claim 2, characterized in that: The mixing ratio of the mixed material and the sulfuric acid solution is 10-15g:200mL; The mass fraction of sulfuric acid solution is 40%.
6. The nanomaterial-containing bridging agent for coating according to claim 5, characterized in that: The rotation speed of the alternating centrifugal treatment is 8000 r / min.
7. The nanomaterial-containing bridging agent for coating according to claim 6, characterized in that: The vacuum drying temperature is 60° C. and the time is 10 min.
8. The nanomaterial-containing bridging agent for coating according to claim 1, characterized in that: The polyisocyanate is a mixture of isophorone diisocyanate and diphenylmethane diisocyanate; Wherein, the mixing mass ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1-2:
1.
9. A method for preparing a bridging agent containing nanomaterials for coatings according to any one of claims 1 to 8, characterized in that: The composite nano material and the base material are added into a mixer according to a certain proportion, and stirred and mixed at a speed of 500 r / min for 30 minutes to obtain.